Corporate real estate decision making : office selection in Sandton Johannesburg - Didiza, Qhama (My University, 2014)
Real estate is said to be the largest or second largest asset in a firm’s financial books – comparable to human resources, but is often been treated as a reactive and secondary utility. Real estate can be a significant factor of production and a strategic resource and due to its effect on an organisation’s profitability there is a growing need for a more critical site selection decision-making. Purpose – This is an exploratory study of the Sandton office market in order to ascertain which factors are most highly considered when making an office (site) selection decision. The purpose of this study is to assist in determining the direction further research into the South African corporate real estate market should take by gathering preliminary information about the preferences of Sandton corporate real estate occupiers. Design/methodology/approach – A questionnaire was developed and distributed electronically through the Survey Monkey website. Findings – The results show that the location factor, in terms of a specific site, is not as highly rated amongst the respondents, as one would expect. The respondents to the questionnaire indicate that the landlord and/or property manager is the most important consideration – whether it is their reputation or their relationship with tenants’ is yet to be determined. Security, a reliable power supply and competitive building levies are amongst some of the most important office attributes for the respondent companies. Originality/value – Sandton’s corporate real estate stock amounts to approximately 168 million square feet, which is comparable in size to Madrid’s total office stock, and greater than cities such as Brussels, Moscow and Milan. Moreover, more than 500 companies in South Africa own corporate real estate, including international companies (Jones Lang LaSalle, 2012) – a large proportion of which is situated in Sandton. These numbers make Sandton a significant player in the international corporate real estate arena.
Keywords: Real estate business--South Africa--Finance.